2005
DOI: 10.4049/jimmunol.175.3.1834
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive Nuclear Expression of the IκB Kinase Complex and Its Activation in Human Neutrophils

Abstract: A singular feature of human neutrophils is that they constitutively express substantial amounts of NF-κB/Rel proteins and IκB-α in the nucleus. In this study, we show that in these cells, IκB kinase α (IKKα), IKKβ, and IKKγ also partially localize to the nucleus, whereas IKK-related kinases (IKKε, TANK-binding kinase-1) are strictly cytoplasmic, and the NF-κB-inducing kinase is strictly nuclear. Following neutrophil activation, IKKβ and IKKγ become transiently phosphorylated in both the cytoplasm and nucleus, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
58
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(70 citation statements)
references
References 70 publications
10
58
1
Order By: Relevance
“…3C). This was also a belated event in comparison with cells stimulated with either LPS or TNF-a, in which IKKg phosphorylation occurs within 5 min (25). Neutrophil pretreatment with 5z-7-oxozeaenol had no effect on IKKg phosphorylation elicited by fMLF (data not shown).…”
Section: Impact Of Tak1 On Fmlf and Gm-csf Signaling In Human Neutropmentioning
confidence: 89%
See 2 more Smart Citations
“…3C). This was also a belated event in comparison with cells stimulated with either LPS or TNF-a, in which IKKg phosphorylation occurs within 5 min (25). Neutrophil pretreatment with 5z-7-oxozeaenol had no effect on IKKg phosphorylation elicited by fMLF (data not shown).…”
Section: Impact Of Tak1 On Fmlf and Gm-csf Signaling In Human Neutropmentioning
confidence: 89%
“…Neutrophils were isolated from the peripheral blood of healthy donors from whom informed consent had been obtained, under a protocol that was approved by an institutional ethics committee, as described previously (25). As determined by Wright staining and nonspecific esterase cytochemistry, the final neutrophil suspensions consistently contained fewer than 0.2% monocytes or lymphocytes, and neutrophil viability exceeded 98% after up to 4 h in culture, as determined by trypan blue exclusion.…”
Section: Cell Isolation and Culturementioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have ascribed a different role for IKK␣ and IKK␤ in the nucleus and cytoplasm of various cell types (33). In this study, we investigated whether acute alcohol exposure affected IKK␣ and IKK␤ protein expression in the nucleus and cytoplasm of human monocytes.…”
Section: Proteolytic Degradation Of Ib␣ By Acute Alcohol Treatment Ismentioning
confidence: 99%
“…IKK␣ was shown to modify histones via phosphorylation, a mechanism essential for the activation of NF-B-directed gene expression (50,51). More recently, it was reported that in primary neutrophils, IKK␣␤␥ and RelA/p65 are constitutively localized to the nucleus, whereas TBK1 and IKK remain exclusively cytoplasmic (52). It remains a possibility that a two-step modification of cRel is required for nuclear translocation and full transcriptional activation.…”
Section: Potential (Reviewed In Ref 21) Direct Phosphorylation Of Nf-bmentioning
confidence: 99%